MENINGKATKAN HASIL BELAJAR IPA MELALUI MODEL KOOPERATIF TIPE PICTURE AND PICTURE PADA SISWA KELAS II SD NATION STAR ACADEMY - Rahmawati, Ery (Jurnal Primary (Kajian Ilmu Pendidikan Dasar dan Humaniora), 2024)
Students still detest science in primary school, especially those in lower classes. This is a result of the teacher not using the appropriate teaching strategy in the classroom and the lesson being delivered simply and unrealistically. Using the picture and picture learning approach, which is a learning model that depends on media pictures, is one of the best ways to address this issue. It requires students to be more engaged, imaginative, and creative in their learning process. The utilization of picture and picture learning methods to enhance low-grade student learning results is the aim of this study. Using class action research (PTK) and a qualitative and quantitative approach. There were two meetings in each of the two cycles that the research was conducted in. This study was conducted at SD Nation Star Academy. The research was conducted in 2 cycles. The result show on the pre action, the students whose learning fulfill the minimum mastery criteria (KKM) was 8 children or 40%. After implemented learning with cooperative learning model type picture and picture in first, the number of students that reached KKM was 13 children or equal to 65%. In second cycle, students who pass the KKM increase to 17 children or 85%. The results showed Picture and Picture Learning Methods proven to improve student learning outcomes with low grades. The role of teachers in applying the method of learning Picture and Picture become the main key